Establishment of Self-Renewable GM-CSF-Dependent Immature Macrophages In Vitro from Murine Bone Marrow - Ito, Sachiko (Public Library of Science, 2013)
Macrophages play a key role in the innate immune system. Macrophages are thought to originate from hematopoietic precursors or the yolk sac. Here, we describe the in vitro establishment of self-renewable GM-CSF-dependent immature macrophages (GM-IMs) from murine bone marrow (BM). GM-IMs grow continuously in vitro in conditioned medium containing GM-CSF. The immunophenotype of GM-IMs is F4/80(high) CD11b(high) CD11c(low) Ly6C(low). By comparing gene expression in GM-IMs and BM dendritic cells, we found that GM-IMs expressed lower levels of chemokines, cytokines and their receptors. GM-IMs are round in shape, attach loosely to non-coated culture dishes and have a marked phagocytic capacity. These results indicate that GM-IMs are macrophage precursor cells. Following stimulation with LPS, monocyte-like GM-IMs converted to flat macrophage-like cells that tightly adhered to non-coated culture dishes and produced pro-inflammatory cytokines TNFα, IL-6 and IL-1β. These results indicated that GM-IMs differentiated to M1 pro-inflammatory macrophages. This was confirmed by stimulation of GM-IMs with IFNγ, an inducer of M1 markers. GM-IMs showed enhanced expression of M2 macrophage markers such as Arg1 and Retnla following stimulation by Th2 cytokines IL-4 and IL-13. When GM-IMs were injected into mice at sites of wounding, wound repair was enhanced. These results indicate that GM-IMs can differentiate to M2 macrophages. When GM-IMs were injected into clodronate-treated mice, they induced resident macrophage proliferation by producing M-CSF. In conclusion we have established self-renewable GM-CSF-dependent immature macrophages in vitro from murine BM, which differentiate to M1 or M2 macrophages.